Selection of VAM Inoculants for Some Forest Tree Species - Rahangdale, Ramesh; Gupta, Nibha (Indian Forester, 1998)
The efficiency of 12 VAM inoculants was evaluated through pot experiment on 6 forest tree species i.e.Albizialebbek, A.procera, Acacianilotica, Dalbergia sissoo, Gmelina arborea and Pongamia pinnata. A singular design with different VAM fungi (Inoculated and uninoculated) was used in the present study. The observation included % root colonization, shoot height, dry biomass and P content in root tissue, after 150 days of plant growth. A significant increase in plant height, dry biomass and tissue 'P' was observed in the VAM inoculated plants. Data recorded during the experiment was treated with Duncun's multiple range test and VAM inoculants for the respective host were selected on the basis of this analysis.